FIFA 11+ Injury prevention in amateur football from development to worldwide dissemination - Bizzini, M.; Junge, A.; Dvorak, J. (Sports injuries and prevention, 2015)
In the last decade injury prevention has received a lot of attention in sports medicine. Recently, international sports governing bodies such as the International Olympic Committee (IOC) have declared the protection of the athletes` health as one of their major objectives. In 1994 the Fédération Internationale de Football Association (FIFA) established its Medical Assessment and Research Centre (F-MARC) with the aim "to prevent football injuries and to promote football as a health-enhancing leisure activity, improving social behaviour". Since then, FIFA has developed and evaluated its injury prevention programmes "The 11" and "FIFA 11+" in several scientific studies, demonstrating how simple exercise-based programmes can decrease the incidence of injuries in amateur football players. This paper summarises 18 years of scientific and on-field work in injury prevention by an international sports federation (FIFA), from formulating the aim to make its sport safer, to the worldwide dissemination of its injury prevention programme in amateur football.